Research on Adulteration Pattern in Different Food Products Sold in the Twin Cities of Hyderabad and Secunderabad-India - Waghray, K.; Gulla, S.; Thyagarajan, P.; Vinod, G. (Current Research in Agricultural and Food Science Vol. 5, 2021)
The adulteration of food has progressed from being a simple means of fraud to a highly sophisticated and lucrative business. Hence the present study was undertaken to identify the adulteration in different food products available in the twin cities of Hyderabad & Secunderabad. Chilli powder samples showed the presence of metanil yellow (8%) added colour (92%) and saw dust (48%). Dry ginger samples (8.33%) showed the presence of an un-permitted coloured dye ultramarine blue. The sweet meat samples showed the presence of aluminum foil (4.3%) instead of silver foil. Coconut burfi samples contained unpermitted color orange II and cotton candy and floss candy showed the presence of rhodamine B. The total percentage of adulteration in the food samples was found to be 49.41%. The adulteration which is been added in the food items can cause tremendous affect on health without our knowledge.